Faktor – Faktor Yang Berhubungan Dengan Konsumsi Buah-Sayur Pada Remaja Di Daerah Rural-Urban, Yogyakarta - Alfonsa Reni Oktavia; Ahmad Syafiq; Asih Setiarini (JURNAL KEPERAWATAN RAFLESIA, 2019)
Vegetable consumption of the Indonesian population is still low in the teen age group both in rural and urban areas. Consumption of fruits and vegetables in adolescents is important for preventing degenerative diseases. The aim of the study was to determine the factors associated with fruit and vegetable consumption in adolescents in rural-urban areas. This study used a cross-sectional research design in Yogyakarta with 196 rural-urban teens. The analysis used was univariate, bivariate, analysis. The results showed that teenagers in urban areas ate less vegetables. Whereas in teenagers in rural areas, they consume less fruit. There is a significant relationship between vegetable consumption in adolescents in rural areas with father's education level (p = 0.031) and self-image perception (p = 0.041), while in urban areas there is a significant relationship between vegetable consumption and self-image perception (p = 0.049) and education in adolescents (p = 0.047). Fruit consumption in adolescents in rural areas that are significantly related is the perception of body image (p = 0.016), while in adolescents in urban areas that are significantly related is monthly money (p = 0.003). Suggestions that can be given are provide health education about the importance of the benefits of vegetables and fruit.